Comparison of IDA and Its Biochemical Markers in Pregnant/Non-Pregnant Women of Rural Areas of Central Maharashtra – A Cross Sectional Study - Hatolkar , V. S.; Deshmukh , Savita (Advancement and New Understanding in Medical Science Vol. 8, 2024)
Toxicity of iron has been considered as one of the risk factors for pregnant women, though it is an essential trace element. Haemoglobin, serum iron, serum ferritin and Total iron binding capacity (TIBC) also plays an important role in the development of fetus. The aim of the present study is to assess the status of above parameters in pregnancy in rural areas. The pregnant women group comprised of 50 healthy pregnant women and 50 healthy non-pregnant women group. Hb% estimated by fully automated 5 part hematology analyzer (Cell Dn Ruby). Serum iron, serum ferritin, and TIBC were measured on fully automated chemistry analyzer. Statistical analysis was carried out in the form of mean±SD, Students ‘t’ test, df and probability. In our study rural pregnant women population showed a significant decrease in mean serum hemoglobin (<10.5 g/dl) as compared to non-pregnant women (13.99 g/dl). Mean serum iron in pregnant women was decreased (73.30±16.74 µg/dl) as compare to non-pregnant women (110.2±17.62 µg/dl). We found decreased mean serum ferritin (9.67±6.2 ng/ml) in pregnant women as compared to non-pregnant women (51.45±23.21 ng/ml), whereas mean serum TIBC level significantly increased pregnant women (476.22±98.36 µg/dl) as compared to non-pregnant women (325.44±70.5 µg/dl) in rural women (p<0.001). This results provides that, it is important to detect which form of iron become abnormal during pregnancy which may lead to cause of nutritional deficiency in pregnant women so as to reduce public problem in rural areas. Thus we recommend ways for increasing public awareness and tackling this health issue including the observance of “National Anemia Awareness and Treatment Day” especially in rural areas of Maharashtra.